Efektivitas Pendidikan Kesehatan Melalui E-File Multimedia Materi KRR dan Tatap Muka di Kelas terhadap Peningkatan Pengetahuan Kesehatan Reproduksi Remaja - Muhamad Arfan, Siswanto Agus Wilopo, Budi Wahyuni (Fakultas Kedokteran Universitas Gadjah Mada, 2010)
Background: Reproductive health has not been fully incorporated into health education in the formal school system due to limited time allocation and teachers. Since media have become an inseparable part of adolescents’ life as more than just their peer, therefore, one alternative in educating adolescents on reproductive health is by using the E-file multimedia of ”The Information, Education and Communication Materials on Adolescent Reproductive Health”.Objective: To examine the effectiveness of adolescent reproductive health E-file multimedia as a method of health education in improving adolescents’ knowledge on reproductive health.Methods: The study was an experimental study designed using quasi experiment. Samples were selected by purposive sampling. Samples were 77 junior high school students. Data were analyzed using t test by applying multiple linear regressions in order to examine the difference in the average scores of adolescents’ knowledge on reproductive health.Results: The average score of health education on reproductive health using multimedia electronic file was 4.31 at deviation standard 1.32 whereas using face to face method in the classroom was 2.5 with deviation standard 1.39. Average difference in both methods was 1.8 at 95% CI (1.19 – 2.42) and p=0.00 or p<0.05.Conclusion: There was no difference between multimedia electronic file method and face to face method in improving knowledge of teenagers about reproductive health.Keywords: health education, knowledge E-file, multimedia, adolescent reproductive health.